Developing a Human Resource Analytics (HRA) competency framework for enhancing Return on Investment (ROI): An empirical investigation - R, Dr. Gayathri (The journal of contemporary issues in business and government, 2022)
The study of the relationship between existing HRA competency and Return on investment (ROI) is a relevant theme. Though the role of employee-related elements of HRA (such as capabilities, motivation and opportunity; CMO) in influencing financial outcomes is relevant, there is no empirical evidence analysing the influence of these variables in the HRA competency-ROI relationship. Using a sample of HR professionals (n = 230) in private organizations in Bangalore, India, this paper tested the hypothesized model using SEM. The present paper examined the mediating effects of capability, motivation and opportunity on the relationship between the existing HRA competency and ROI. Likewise, this study tested the differential effect of capability, motivation and opportunity on ROI. The findings of the study identified a positive and significant relationship between existing HRA competency, employee motivation and ROI. Besides, ‘opportunity’ was identified as a significant mediator of the link between existing HRA competency and ROI. Concerning the differential effect of the individual employee-related variables, the present study revealed that ‘opportunity’ was more strongly related to ROI than ‘motivation’. As one of the first, this paper presents a framework that explains how HRA competency influences ROI through CMO.